Clinical development of CAR T cells—challenges and opportunities in translating innovative treatment concepts. Issue 9 (1st August 2017) - Hartmann, Jessica; Schüßler‐Lenz, Martina; Bondanza, Attilio; Buchholz, Christian J
Abstract: Chimeric antigen receptor (CAR) T cell therapy, together with checkpoint inhibition, has been celebrated as a breakthrough technology due to the substantial benefit observed in clinical trials with patients suffering from relapsed or refractory B‐cell malignancies. In this review, we provide a comprehensive overview of the clinical trials performed so far worldwide and analyze parameters such as targeted antigen and indication, CAR molecular design, CAR T cell manufacturing, anti‐tumor activities, and related toxicities. More than 200 CAR T cell clinical trials have been initiated so far, most of which aim to treat lymphoma or leukemia patients using CD19‐specific CARs. An increasing number of studies address solid tumors as well. Notably, not all clinical trials conducted so far have shown promising results. Indeed, in a few patients CAR T cell therapy resulted in severe adverse events with fatal outcome. Of note, less than 10% of the ongoing CAR T cell clinical trials are performed in Europe. Taking lead from our analysis, we discuss the problems and general hurdles preventing efficient clinical development of CAR T cells as well as opportunities, with a special focus on the European stage. Abstract : Authoritative, insightful overview of the problems and general hurdles preventing efficient clinical development of chimeric antigen receptor (CAR) T cell therapy for cancer as well as future opportunities.